'Behavioral modernity' as a process, not an event, in the human niche. (3rd April 2018) - Kissel, Marc; Fuentes, Agustín
ABSTRACT: The search for 'firsts' is a common trope in the study of human evolution. Both popular books and scientific articles attempt to discern the key moments in evolutionary history that indicate the true appearance of our species (or subspecies, depending on one's classificatory scheme). While scientists are cognizant of the problematic nature of this work, we often use a specific set of dates and material markers as tipping points for the origins and spread of modern humans. Here, we summarize the available data used to indicate behavioral modernity and suggest (1) that key factors traditionally seen as indicative of 'behaviorally modern' humans had their origin across the Middle Pleistocene and (2) were not lumped into one cohesive package (or associated with only one species) until more recently. Fossil, genetic, and archaeological datasets indicate that members of our genus ( Homo ) have been engaging in complex cognitive thought and semiosis since circa 400–300 ka, and perhaps earlier. These data point to a more complex, but more accurate and realistic, depiction of the braided steam of human evolution.